Comparison of mothership versus drip-and-ship models in treating patients with acute ischemic stroke: A systematic review and meta-analysis. Issue 2 (February 2022) - Mohamed, Ahmed; Fatima, Nida; Shuaib, Ashfaq; Saqqur, Maher
Introduction: There is controversy if direct to comprehensive center "mothership" or stopping at primary center for thrombolysis before transfer to comprehensive center "drip-and-ship" are best models of treatment of acute stroke. In this study, we compare mothership and drip-and-ship models to evaluate the best option of functional outcome. Methods: Studies between 1990 and 2020 were extracted from online electronic databases. Clinical outcomes, critical time measurements, functional independence, and mortality were then compared. Results: A total of 7824 patients' data were retrieved from 13 publications (3 randomized control trials and 10 retrospective ones). In addition, 4639 (59.3%) patients were treated under mothership model, and 3185 (40.7%) followed the drip-and-ship model with mean age of 70.01 ± 3.58 versus 69.03 ± 3.36; p < 0.001, respectively. The National Institute Health Stroke Scale was 15.57 ± 3.83 for the mothership and 15.72 ± 2.99 for the drip-and-ship model (p ≤ 0.001). The mean symptoms onset-to-puncture time was significantly shorter in the mothership group compared to the drip-and-ship (159.69 min vs. 223.89 min; p ≤ 0.001, respectively). Moreover, the collected data indicated no significant difference between symptom's onset to intravenous thrombolysis time and stroke onset-to-successful recanalization time (p = 0.205 and p ≤ 0.001, respectively). Patients had significantly worse functional outcome (modified Rankin score) (3–6) at 90 days in the drip-and-ship model (odds ratio (OR): 1.47, 95% confidence interval (CI): 1.13–1.92, p < 0.004) and 1.49-folds higher likelihood of symptomatic intracerebral hemorrhage (OR: 1.49, 95% CI: 1.22–1.81, p < 0.0001) compared to mothership. However, there were no statistically significant difference in terms of mortality (OR: 1.16, 95% CI: 0.87–1.55, p = 0.32) and successful recanalization (OR: 1.12, 95% CI: 0.76–1.65, p = 0.56) between the two models of care. Conclusion: Patients in the mothership model have significantly improved functional independence and recovery. Further studies are needed as the data from prospectively randomized studies are not of sufficient quality to make definite recommendations.